1972
DOI: 10.1128/jb.111.3.690-695.1972
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Saccharomyces cerevisiae Cell Wall Mannan Chemotypes

Abstract: We have obtained evidence for two structurally and antigenically different Saccharomyces cerevisiae cell wall mannans. One, which occurs widely and is found in S. cerevisiae strain 238C, is already known to be a neutral mannan which yields mannose, mannobiose, mannotriose, and mannotetraose on acetolysis of the (1 a 6)-linked backbone. The other, which was found in S. cerevisiae brewer's strains, is a phosphomannan with a structure very similar to that of Kloeckera brevis mannan. S. cerevisiae (brewer's yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Rosenfeld and Ballou (20) reported that S. cerevisiae X2180 phosphomannan, with a mannose-to-phosphate ratio of 38, contained phosphorylated side chains. Furthermore, S. cerevisiae 1406 phosphomannan, with mannose-to-phosphate ratio of 19, possess a mannosylphosphorylmannotriose side chain, in which the mannosylphosphate group is immunodominant (5). These strains can be assumed to be different serotype from serotype la, although these strains remain to be serotyped.…”
Section: Determinantmentioning
confidence: 99%
See 2 more Smart Citations
“…Rosenfeld and Ballou (20) reported that S. cerevisiae X2180 phosphomannan, with a mannose-to-phosphate ratio of 38, contained phosphorylated side chains. Furthermore, S. cerevisiae 1406 phosphomannan, with mannose-to-phosphate ratio of 19, possess a mannosylphosphorylmannotriose side chain, in which the mannosylphosphate group is immunodominant (5). These strains can be assumed to be different serotype from serotype la, although these strains remain to be serotyped.…”
Section: Determinantmentioning
confidence: 99%
“…On the other hand, Suzuki et al (21) analyzed the determinant group of S. cerevisiae X2180 mannan by the precipitin-inhibition assay using mannooligosaccharides as inhibitory haptens. Their results indicated that the mannotetraose, ( (5) established that the a-n-mannosylphosphate unit was also the major antigenic determinant in the side chains of some other strains of S. cerevisiae. Furthermore, Ballou et al (2) reported the generalized structures for the mannans of S. chevalieri, S. italicus, S. diastaticus, and S. carlsbergensis, all of which are now synonyms for S. cerevisiae (26), and indicated that in the S. cerevisiae system, the terminal a(1-3)-linked mannose unit was the principal immunochemical determinant on the cell surface.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Further aspects regarding co-floccula tion in ale yeast strains will be discussed later. 3. Strains flocculent on their own after growth in wort (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Various authors have identifi ed the phosphorylated side chains of the yeast mannoproteins, responsible for the negative charges of yeast surface, and have reported slight differences between S. cerevisiae strains. [38][39][40] On carrying out the same experiment with magnetic stirring, an increase in the sorption of both compounds was observed in comparison with the unstirred samples; the sorption was more important in the case of 4-ethylphenol than in the case of 4-ethylguaiacol. The concentration of 4-ethylphenol, after reaching the equilibrium in the experiment with stirring diminished compared to the control sample (15.1%), and in the case of 4-ethylguaiacol this reduction was somewhat lower (12.1%) (Figures 3a, 3b).…”
Section: Sorption Experimentsmentioning
confidence: 99%